ВИХОВНІ ФУНКЦІЇ МОЛОДІЖНОЇ МУЗИЧНОЇ СУБКУЛЬТУРИ В СТАНОВЛЕННІ ДУХОВНОСТІ СТАРШОКЛАСНИКА (Педагогіка вищої та середньої школи, 2002)
The definite explanation of the conception of subculture has been exposed, and the causes of its origin, its components, and its specific peculiarities have been considered. The educational functions of musical subculture of youth for forming of senior pupil's spirifmillts have been done.